HIGH-VOLUME PLASMAPHERESIS IN CARDIAC AND AORTIC SURGERY - I. N. Solovievа; Yu. V. Belov (Вестник анестезиологии и реаниматологии)
Prevention and treatment of multi-organ failure after complicated surgeries on heart and major vessels remain to be crucial.The objective: to evaluate the potential use and efficiency of high-volume plasmapheresis for prevention and early therapy of multiple organ failure syndrome.Methods: high-volume plasmapheresis was used in 246 patients with the most disseminated complications of the peri-operative period. Plasmapheresis was done during the first 4–6 hours after surgery (157 patients) and in 6–12 hours after surgery (41 patients) and later than 12 hours (48 patients).Results. After complicated surgeries with in vitro hemoperfusion, the activation of system inflammatory response and endotoxicosis was more intensive versus patients with no complications. Plasmapheresis in 4–6 hours after surgery promoted metabolic normalization and in the majority of cases prevented of multiple organ failure (if at least 50% of circulating plasma was removed). After early plasmapheresis, the level of markers of system inflammatory response and endotoxicosis reduced by 28–30%, which allowed preventing serious renal disorders and cytolysis manifestations.Conclusion: Post-operative high-volume plasmapheresis performed in 4–6 hours after complicated cardiac surgeries is effective for prevention of multiple organ failure syndrome in 64% of cases.